2007
DOI: 10.1002/chin.200722235
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Methods in the Synthesis of Macrocyclic Schiff Bases

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Idealized H atoms were refined with isotropic displacement parameters set to 1.2 (1.5 for methyl groups) times the equivalent isotropic U values of the parent atoms. The lattice water molecules are disordered over three sites, with occupancies of 0.40(1), 0.40(1), and 0.20 (1). The crystallographic data for the complex are listed Table 1.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Idealized H atoms were refined with isotropic displacement parameters set to 1.2 (1.5 for methyl groups) times the equivalent isotropic U values of the parent atoms. The lattice water molecules are disordered over three sites, with occupancies of 0.40(1), 0.40(1), and 0.20 (1). The crystallographic data for the complex are listed Table 1.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…[1][2][3] In the last few decades, metal complexes with Schiff bases have attracted considerable attention due to their remarkable biological activity, such as antifungal, antibacterial, and antitumor. [4][5][6] It has been shown that the Schiff base complexes derived from salicylaldehyde and its derivatives, bearing the N 2 O, N 2 S, NO 2 , or NSO donor sets, have interesting biological activity, [6][7][8] however, the metal complexes and the biological activity of the Schiff base 2-ethoxysalicylaldehydethiosemicarbazone (HL; Scheme 1) de- rived from 3-ethoxysalicylaldehyde and thiosemicarbazide, has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In particular, the molecule/anion recognition has attracted increasing interest. [4][5][6][7][8] For example, we have reported several macrocyclic complexes, which could recognize and fix deprotonated imidazole molecule, and act as model compounds of Cu 2 Zn 2 -SOD.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In recent years, metal complexes of Schiff bases have attracted considerable attention due to their interesting biological activity, such as antifungal, antibacterial and antitumor. [4][5][6] Schiff base complexes derived from salicylaldehyde and its derivatives with primary amines, bearing the N 2 O, N 2 S, NO 2 or NSO donor sets, have particular biological activities.…”
Section: Introductionmentioning
confidence: 99%